2011
DOI: 10.1016/j.pestbp.2010.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral effects of acute exposure to the insecticide fipronil

Abstract: The effects of fipronil (Frontline Ò Top Spot) were investigated in 40 days old rats utilizing open field (OF), hole-board (HB) and elevated plus-maze (EPM) apparatus. Rats (N = 15) received topical application of fipronil (70, 140 and 280 mg/kg) in the neck region and behavior was tested 3 h after administration. Animals treated with corn oil (vehicle) were used as controls. In the OF test animals treated with fipronil at 140 mg/kg showed increased rearing, whereas animals exposed to 280 mg/kg showed increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 36 publications
2
18
0
2
Order By: Relevance
“…Earlier studies have reported that liver, kidney and brain are the target organs for toxic insults of fipronil (Badgujar et al, 2015;Terç ariol and Godinho, 2011), owing to the fact that these tissues are extremely perfused organs and receive high blood volumes. In fact, liver toxicity to fipronil has been reported in mice following subchronic and chronic exposures (De Oliveira et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have reported that liver, kidney and brain are the target organs for toxic insults of fipronil (Badgujar et al, 2015;Terç ariol and Godinho, 2011), owing to the fact that these tissues are extremely perfused organs and receive high blood volumes. In fact, liver toxicity to fipronil has been reported in mice following subchronic and chronic exposures (De Oliveira et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Jackson et al (2009) have suggested that the "no observed adverse effect level" (NOAEL) for acute oral dose of fipronil in rats is 2.5 mg/kg. Importantly, recent evidences have shown that fipronil may be a potent toxicant affecting non-target organisms, including environmental species populations and potentially humans (Le Faouder et al, 2007) and deleterious effects were observed on the early stages of the animal development (Udo et al, 2014;Badgujar et al, 2015;Terç ariol and Godinho, 2011). Although the fipronil's actions are blocking the gamma-aminobutyric acid (GABA)-ergic receptors and glutamate (Glu)-gated chloride channels (Narahashi et al, 2007;Zhao et al, 2005), concerningly, evidence has demonstrated that fipronil induces the releasing of reactive oxygen species, resulting in increased oxidative stress (Overmyer et al, 2007;Vidau et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The number of head dips and the duration of each head dip (seconds) were recorded for 5 min. One head dip was considered as an animal having both eyes into a hole [40]. The testers were kept blind to the treatment procedures to minimize observational bias.…”
Section: Exploratory Behaviormentioning
confidence: 99%
“…However, using this insecticide may lead to formation of toxic metabolites in the environment (Gunasekara et al, 2007), such as sulfone and desulfinyl, which are photodegradation products reported as toxic for insects, mammals, fishes, and birds (Das et al, 2006). In addition, it is also known that exposure to pesticides is neurotoxic to rodents and other mammals, including humans (Terçariol & Godinho, 2011) due to their wide commercial and domestic uses (Tingle et al, 2003).…”
Section: Bioacumulação De Inseticida Em Agaricus Subrufescensmentioning
confidence: 99%